Improving Student Learning Outcomes in Mathematics Learning Using The Cooperative Model of Think Pair Share Type (TPS) in Middle School - Preyantini Preyantini (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
The cooperative model of think pair share (TPS) type is one of the cooperative learning models designed to invite students to find answers to questions from a concept through a group. One of the problems faced in learning Mathematics is the low learning outcomes of students, this is due to the learning process at school, which is still teacher-centered. This study aims to determine whether the cooperative model type think pair share (TPS) can improve student learning outcomes in mathematics learning in seventh grade SMPN 24 Pontianak. This type of research is a class action research (PTK) with 3 cycles. Data collection techniques in this study used IPKG and test/evaluation. The results of the study obtained student learning outcomes in learning mathematics with the TPS type cooperative learning model have increased, for the average value of student learning outcomes, cycle 1 was 76.67, cycle 2 reached 77.33 and cycle 3 reached 80.50, while for the percentage of student learning outcomes completeness, cycle 1 there were 66.67% (10 students) completed learning, cycle 2 reached 80.00% (12 students) completed learning, and cycle 3 reached 86.67% (13 students) completed learning. These results indicated the success in learning mathematics with the Think Pair Share (TPS) type cooperative model, because it has met the success criteria ≥ 75% of all students have reached passing grade. So it can be concluded that there is an increase in student learning outcomes in mathematics learning using the Think Pair Share (TPS) type cooperative model in seventh grade.